Impact of the implementation of EU, national and local policies and legislation on the transition towards eco-cities in Poland - Kociuba, Dagmara; Wajs, Klaudia (Bulletin of Geography. Socio-economic Series, 2021)
Transforming cities towards eco-cities constitutes a significant effort in mitigating and adapting to climate change. The implementation of legal acts and diverse environmentally oriented sectoral policies plays an important role in that process. The objective of this paper is to determine the antecedences and effects of the transformation of cities in accordance with the eco-city concept in Poland in the context of implemented policies, legislation and initiatives. The study reviews the normative acts and programme-strategic documents that provide the framework for the shift towards eco-city at the international and EU level, as well as identifying changes in legislation and policy initiatives resulting from their implementation at national and local level. A set of 24 original indices referring to six aspects of the eco-city (waste management, water and wastewater management, transport and urban mobility, application of RES in energy engineering, air quality, and urban green areas) were applied in multi-criterion analyses in selected case studies. This permitted us to identify the key factors that power the transition towards eco-city. The legal and policy measures are implemented in a top-down approach. Actions are usually initiated at national level and implemented by local authorities, who operate according to their assigned tasks and using dedicated tools (e.g. LEPs, SUMPs). Significant effect of the implementation of eco-city solutions were identified in waste management, sustainable transport, urban mobility, and air quality improvement. Recommendations for future measures include implementing plans and demonstrative projects of eco-cities or eco-districts, conducting complex pro-ecological measures, and increasing the role of bottom-up actions